Deep femoral artery: A new point of view based on cadaveric study - Claassen, Horst; Schmitt, O.; Schulze, M.; Wree, A. (Annals of Anatomy-Anatomischer Anzeiger, 2021)
Introduction: In diagnostic angiographic procedures, the knowledge of arterial variations in the femoral artery (FA), deep femoral artery (DFA) and lateral and medial circumflex femoral arteries (LCFA, MCFA) has a great impact. Material and methods: The frequency of branching patterns of these arteries was investigated in 111 thighs of body donors. Gender and side differences were analyzed statistically. Results: The median distance of separation of the DFA from the FA in relation to the inguinal ligament (IL) was 3.29 cm. High origins (1−2 cm below IL) and middle origins (3−5 cm below IL) of the DFA were found in an equal distribution of 39.3% and 41.1%, respectively. Low origins (6−10 cm below IL) were rare (19.6%) but showed a tendential significance toward expression in males (p = 0.096). The origin of the LCFA from the FA (19.8%) or DFA (70.2%) are in line with the findings of other groups. The origin of the MCFA from FA (14.4%) or DFA (74.7%) showed that circumflex femoral arteries arose mostly from DFA. A trifurcation of the FA into the DFA, LCFA and MCFA was only observed in 9.9% and, therefore, less frequently than reported by others. Branches of the femoral nerve (FN) passed mostly anterior (46.4%) or anterior and posterior (47.8%) to the LCFA. The rare constellation of branches of FN passing only posterior to the LCFA (5.8%) showed a tendential significance to left side expression (p = 0.084). Conclusions: Taken together, this is the first classification of the median distance of separation of the DFA from the FA in relation to the IL in three defined groups. The knowledge of DFA branching pattern is essential for recent therapy options of cardiac diseases using a femoral artery access: transcatheter aortic valve replacement, catheter-based miniaturized ventricular assist device and veno-arterial extracorporal membrane oxygenation. The variant topography of the branches of FN in relation to LCFA should be kept in mind when harvesting an anterolateral thigh flap.
CRIS-Team Scopus Importer:2021-04-16
Keywords: Arterial variation; Branching pattern; Femoral arteries; Femoral nerve; Thigh

Teaching anatomy under COVID-19 conditions at German universities: recommendations of the teaching commission of the anatomical society - Böckers, Anja; Claassen, Horst; Haastert-Talini, Kirsten; Westermann, Jürgen (Annals of Anatomy-Anatomischer Anzeiger, 2021)
Background: In this viewpoint representatives of the Teaching Commission of the Anatomical Society summarize their teaching experiences gained during the COVID-19 pandemic in the summer term of 2020 and derive first recommendations concerning face-to-face and remote teaching of anatomy for the future. Methods: Representatives of the Teaching Commission of the Anatomical Society met virtually, exchanged experiences and summarized them in writing and answered a short questionnaire. Results: The required transition to remote learning during summer term of 2020 was possible, but revealed technical shortcomings and major deficits concerning practical hands-on teaching. Conclusion: The Teaching Commission of the Anatomical Society recommends that universities should follow the idea of as much face-to-face teaching as possible and as much online teaching as necessary for future terms.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Anatomy teaching; COVID-19 pandemic; Face-to face-learning; Remote learning